The Fantastical Body and the Vulnerability of Comfort: Alternative Models for Understanding Body Image - Springgay, Stephanie (Alberta Journal of Educational Research, 2009)
Arguing for new models of inquiry that interrogate body image from the perspective of intercorporeality, this article explores a research study conducted in a secondary school art class. Shifting analysis from the representation of body image to a tactile, sensuous, and experiential understanding of body image, I highlight the contradictions and tensions at work in understanding students’ experiences of body knowledge. The article poses possibilities for thinking further about how pedagogy might work with and against the contradictions of body image.